2021
DOI: 10.3389/fneur.2021.657004
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Interfaces: The COVID-19 Pandemic and Depression

Abstract: Since the start of the spread of the coronavirus disease 2019 (COVID-19) pandemic, an international effort has sought to better characterize associated extra-pulmonary health sequelae. The acute and or chronic detrimental impact of SARS-CoV-2 infection on mental health, especially depression, is increasingly described. Simultaneously the pandemic has influenced depressive symptomatology by modifying economic, social and political structures, in addition to affecting daily routines. In both cases, associated im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 142 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…To date, many studies have described an increased level of IL-10 in COVID-19 patients [84][85][86]. In severe cases, the level of IL-10 was higher than in mild cases, and positively correlated with mortality due to COVID-19 [47,85,[87][88][89].…”
Section: Il-10mentioning
confidence: 98%
See 2 more Smart Citations
“…To date, many studies have described an increased level of IL-10 in COVID-19 patients [84][85][86]. In severe cases, the level of IL-10 was higher than in mild cases, and positively correlated with mortality due to COVID-19 [47,85,[87][88][89].…”
Section: Il-10mentioning
confidence: 98%
“…For COVID-19, the research also diverges. Many studies have shown an increase in the concentration of IFN-γ [84,90,91,105,134,139,140,[144][145][146], however, several studies showed a decrease [47,147,148]. In some studies, the severity of COVID-19 positively correlated with the level of IFN-γ [88,89,131].…”
Section: Ifn-γmentioning
confidence: 98%
See 1 more Smart Citation
“…nancial repercussions) and/or biological consequences of infection is unclear. Neuro-in ammation is one possible biological mechanism by which COVID-19 infection could lead to depression-anxiety (Perlmutter 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, involvement of the peripheral nervous system (PNS) and autonomic nervous system (ANS) results in an imbalance between SNS and PSNS with the development of SS ( 23 ). The imbalance of the SNS/PSNS axis of ANS may affect the release of pro-inflammatory cytokines and immune-inflammatory response during Covid-19 ( 24 ). In this context, high circulating catecholamine levels may reflect sympathetic-mediated neutrophilia and T cell dysfunction in Covid-19 due to SS ( 25 ).…”
Section: β-Blockers and Sympathetic Storm In Covid-19mentioning
confidence: 99%